The institutionalist movement in American economics, 1918-1947 : science and social control - Rutherford, Malcolm, 1948- (Cambridge : Cambridge University Press, 2011)
This book provides a detailed picture of the institutionalist movement in American economics concentrating on the period between the two World Wars. The discussion brings a new emphasis on the leading role of Walton Hamilton in the formation of institutionalism, on the special importance of the ideals of 'science' and 'social control' embodied within the movement, on the large and close network of individuals involved, on the educational programs and research organizations created by institutionalists and on the significant place of the movement within the mainstream of interwar American economics. In these ways the book focuses on the group most closely involved in the active promotion of the movement, on how they themselves constructed it, on its original intellectual appeal and promise and on its institutional supports and sources of funding.
Part 1. Introduction: 1. American institutionalism in the history of economics; 2. Understanding institutional economics -- Part II. Institutionalist Careers: 3. Walton Hamilton: institutionalism and the public control of business; 4. Morris A. Copeland: institutionalism and statistics -- Part III. Centers of Institutional Economics: 5. Institutionalism at Chicago and beyond; 6. Amherst and the Brookings Graduate School; 7. Wisconsin institutionalism; 8. Institutional economics at Columbia University; 9. The NBER and the foundations -- Part IV. Challenges and Changes: 10. The institutionalist reaction to Keynesian economics; 11. Neoclassical challenges and institutionalist responses -- Part V. Conclusion: 12. Institutionalism in retrospect.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Hamilton, Walton Hale, -- 1881-1958.; Institutional economics -- History -- 20th century; Economics -- United States -- History -- 20th century